Population census and information registers: traditions vs innovations - Andrichenko, Ludmila V.; Plyugina, Inna V. (Journal of the Belarusian State University. Law, 2024)
Modern scientific and technological achievements, introduced into the mechanism of public administration, make it possible to improve the tools used to ensure state tasks and functions, and to make a transition to a qualitatively different level of regulatory influence. At the same time, a revision of the used methods and means is carried out in order to update them. In recent years, the scientific and expert community has been discussing the feasibility of using censuses to obtain information about the population, given the increasing distribution of information registers that make it possible to quickly obtain up-to-date and reliable information about persons located on the territory of the state. It is noted that conducting a census is associated with significant time and organisational costs, the obtained data is not always reliable it, does not fully reflect the current situation, and is partly replenished from information from the same information registers, etc. At the same time, information registers include a narrower list of information than that obtained during the census, and do not involve direct interaction with the population. The article analyses the above arguments in a legal context (taking into account the legislation of the Russian Federation), and offers the author’s assessment of the feasibility of the simultaneous use of these tools in modern realities.